Dissociative Electron Attachment to Bromotrifluoromethane - Stefán Þór Kristinsson 1991- (2014)
The interaction between molecules and low energy electrons often leads to the production of transient negative ions (TNIs) through electron capture. These ions are formed in an excited state and are therefore bound to relax. They do so mostly through two competing channels. The molecule can reemit the trapped electron, through autodetachment (AD), or bonds can be ruptured to form a negatively charged molecular fragment and its neutral counterparts. The latter process is called dissociative electron attachment (DEA). DEA behavior, that takes place when bromotrifluoromethane, CF3Br, interacts with electrons of energy below the molecule’s ionization limit, was studied. The fragment formation from CF3Br was examined using a crossed molecular and electron beam apparatus termed SIGMA, set up at the University of Iceland. The dissociation behavior of the molecule was compared and contrasted to calculated thermochemical threshold values as well as the behavior of congeners, CF3I and CF3Cl, that have been previously studied. A total of four negative fragments, Br–, F–, FBr– and CF2Br–, were detected, proceeding through three different resonances. Peaks in the negative ion yields were observed around 0 eV, 4 eV and 8 eV. The resonance close to 0 eV yields exclusively negative bromine ions and that peak is the most intense by far, measured at a count rate of more than three orders of magnitude larger than the next. Peaks close to 0 eV can also be observed in negative ion yields for the other three fragments, but they were attributed to other causes than the formation of the anion from primary dissociation of the molecule. A resonance at 4 eV yields all four fragments with different intensity peaks. A peak at 8 eV was also detected with low intensity in the ion yields for Br– and F–. Þegar sameindir víxlverka við lágorkurafeindir myndast oft tímabundið neikvætt hlaðnar jónir í gegn um föngun rafeinda. Þessar jónir myndast í örvuðu ástandi og þurfa að losa orku. Þær gera það aðallega með tveim leiðum sem eru í samkeppni ...